SISTEM INFORMASI DINAS KELAUTAN DAN PERIKANAN PROVINSI NUSA TENGGARA TIMUR BERBASIS WEBSITE - Laurens, Averian Tanauw (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2022)
The marine and fisheries service of the province of East Nusa Tenggara is one of many institutions or agencies whose functions, duties, and positions are regulated or controlled by law. The marine and fisheries service is the driving factor or organizer in the marine and fisheries segment led by the head of the service who is responsible for the governor through the regional secretary. The marine and fisheries service implements the use of technology such as computers and other electronic devices to facilitate the continuation of work activities and it is necessary to present relevant information to the Marine and Fisheries Service of the East Nusa Tenggara province so that it is known and known by the people of East Nusa Tenggara. From the above basis, the problem is how to build a website as a medium of information at the Department of Marine Affairs and Fisheries of East Nusa Tenggara Province. There is a method used, namely the Waterfall method, the waterfall method is one type of application development model and is included in the classic life cycle, which emphasizes sequential and systematic phases. For the development model, it can be analogous to a waterfall, where each stage is carried out sequentially from top to bottom. The expected result of this research is that the website built by the author for the Department of Marine Affairs and Fisheries of East Nusa Tenggara Province can be successful so that it can provide benefits to the Department of Marine Affairs and Fisheries of East Nusa Tenggara Province in providing information to the public related to everything related to the Department of Marine Affairs. and Fisheries in the Province of East Nusa Tenggara and can also facilitate the people of East Nusa Tenggara in accessing information about the Department of Marine Affairs and Fisheries of the Province of East Nusa Tenggara